Arson Measurement, Analysis, and Prevention in Massachusetts, 1983-1985 - Fox, James Alan ([Verlag nicht ermittelbar], 1993)
These data were gathered to test a model of the socioeconomic and demographic determinants of the crime of arson. Datasets for this analysis were developed by the principal investigator from records of the Massachusetts Fire Incident Reporting System and from population and housing data from the 1980 Census of Massachusetts. The three identically-structured data files include variables such as population size, fire incident reports, employment, income, family structure, housing type, housing quality, housing occupancy, housing availability, race, and age.